Effectiveness of marine algae (Gracilarias sp) in the treatment of periodontitis: Efektivitas Alga Laut (Gracilaria sp) dalam Perawatan Periodontitis - Irene E. Rieuwpassa; Sasmita; Nur Ain latjompoh; Amani Fajri Khairunnisa; Astriani (Makassar Dental Journal, 2024)
Periodontal disease is an inflammatory response due to bacterial infection of the supporting tissues of the teeth. Porphyromonas gingivalis is a gram-negative anaerobic bacterium associated with periodontal disease. An adjunctive therapy to mechanical pe-riodontal therapy is the use of antibiotics, although long-term use can cause some hypersensitivity effects, toxic reactions. Many bacteria are resistant to antibiotics, so in this study Gracilaria extract was chosen as an additional therapy to reduce the effects of resistance to antibiotics. extract as an additional therapy to reduce the effects of such resistance. Gracilaria has carotene con-tent which has very important biological functions as an antioxidant, and immunostimulator that can prevent disease, anti-inflamma-tory, anti-stress, anti-aging, and skin protection from ultraviolet light. ultraviolet rays. Gracilaria also has the ability to capture free radicals. Gracilaria contains antibacterial bioactive compounds, namely alkaloids, flavonoids, and steroids that can inhibit the growth of P.aeruginosa and Staphylococcus. This paper explores the effectiveness of Gracilaria sp in the treatment of periodontitis.